Evaluation of Bacterial Population in the Saliva of Drug Addicts - Zahoor, Muhammad; Uddin, Jalal (Journal of Dentistry And Oral Implants, 2018)
Background: The human mouth harbors over 700 microbial genera. The large number of them is normal bacteria; few of them are opportunistic pathogens. Objective: The study was aimed to evaluate the bacterial population of drug addicted persons and compare it to that of a normal healthy person. Methods: Five different samples of human saliva; alcohol drunken person, oral moist snuff user, cigarette, hashish and shisha smoker were investigated the involvement of bacteria in them. One sample was collected from normal non-addict person. The bacterial population in drug addictive persons were compared that on normal non-addictive person. Results: The bacteria observed were: Gram negative cocci, mono cocci, streptococci, vibrio, gram negative rod, gram positive staphylococcus, gram positive streptococci and gram-positive rod. Conclusion: The order of bacterial population was; alcohol drunken person<oral moist snuff user ˂ cigarette smoker ˂ hashish smoker ˂ shisha smoker˂ normal non addictive person. From the findings in this study it is concluded that all these drugs have some antibacterial activities.
Keywords: Cigarette; hashish; oral moist snuff; shisha